UJI KEKUATAN PELAT BERSIRIP YANG DIPERKAKU DENGAN CARA PENEBALAN DI DAERAH SAMBUNGAN ANTARA PELAT DAN SIRIP (STUDI KASUS: PENEBALAN PADA PELAT) - Setiawan, Marius; Yusuf, M; Bachtiar, Vivi (Jurnal Mahasiswa Teknik Sipil Universitas Tanjungpura, 2018)
Soil peat in Pontianak City, West Kalimantan have a low soil bearing capacity. This has an impact on the pavement system that has been built. The transfer of asphalt pavement system to concrete pavement has been widely applied. But still that, the road is still damage. The purpose of this research is to obtain optimum soil bearing capacity of pavement finned concrete pavement plate structure which given thickening in plate and connection area. The variable under review is thickening on the inner side of the connection between the joint and the fin. The research was conducted by loading test method in laboratory using UTM. The result showed that with the thickening there is an increase in carrying capacity of the plate. However, there is a limit to the addition of thickening of the fins if the plate fin is too thick, then the strength of the carrying capacity of the plate is reduced.Keywords :Â finned concrete plates, plate thickening, optimum carrying capacity